Metamizole use during first trimester—A prospective observational cohort study on pregnancy outcome. Issue 10 (3rd August 2017) - Dathe, Katarina; Padberg, Stephanie; Hultzsch, Stefanie; Meixner, Katja; Tissen‐Diabaté, Tatjana; Meister, Reinhard; Beck, Evelin; Schaefer, Christof
Abstract: Introduction: The analgesic metamizole (dipyrone) is not recommended during pregnancy due to limited experience. In several countries, metamizole has no market authorization because of agranulocytosis as a rare but severe adverse effect. However, in others, metamizole is available and widely used as a pain reliever, and its use occurs also during pregnancy, often followed by fears of potential teratogenic risk. Methods: This prospective observational cohort study compared pregnancy outcomes of 446 women exposed with metamizole in the first trimester with a randomly selected control cohort comprising 887 women not exposed to metamizole. Relevant data were obtained via structured questionnaires applied during the first trimester and 2 months after the expected date of birth between January 2000 and December 2015. Results: The rate of major birth defects (7/373, 1.9%) was not increased in the metamizole cohort (OR adjusted 1.15, 95% CI 0.4‐3.5). The cumulative incidences for spontaneous abortions did not reveal a significant difference between the exposed (12.2%, 32/446) and comparison cohort (19.4%, 77/887) (HR adjusted 0.72, 95% CI 0.5‐1.1). Elective terminations of pregnancy (ETOP), mostly for "social" reasons, were more frequent in the metamizole (12.5%, 45/446) than in the comparison cohort (9.4%, 50/887; HR adjusted 1.48, 95% CI 0.98‐2.2). Conclusions: Metamizole exposure in the first trimester does not seem to bear a substantial teratogenic risk. Our study results support reassurance in those instances where metamizole has been used during an unrecognized pregnancy or where its use appears indispensable.